Social Cognition in Autism Spectrum Disorder Across the Adult Lifespan: Influence of Age and Sex on Reading the Mind in the Eyes Task in a Cross-sectional Sample - Pagni, Broc A.; Walsh, Melissa J. M.; Rogers, Carly; Braden, B. Blair (Frontiers in Integrative Neuroscience, 2020)
Background: Approximately 50,000 U.S. teens with autism spectrum disorder (ASD) become adults every year, however little is known regarding how age influences social cognition and if men and women with ASD are differentially impacted across the adult lifespan. Social cognition declines non-linearly with age in neurotypical (NT) adults. Moreover, sex differences have been observed on RME tasks in NT adults but not adults with ASD, although aging effects have been largely ignored. Objective: This cross-sectional study examined the influence of age and sex on social cognition in adults with ASD compared to NT adults. Methods: The Reading the Mind in the Eyes (RME) task was administered to evaluate theory of mind abilities in 95 adults with ASD and 82 NT adults ages 18-71 years. Main effects of diagnosis, age, and sex, as well as two-way and three-way interaction were modeled using linear and quadratic aging terms in a multiple regression analysis. Results: A main effect of diagnosis was observed, indicating poorer performance in adults with ASD relative to NT adults. Age and sex interactions were nonsignificant. Discussion: We replicated previous findings of reduced ToM abilities in adults with ASD, compared to NT adults. While interactions were nonsignificant, visual inspection of quadratic age curves indicated the possibility of unique ToM trajectories in men and women with and without ASD that should be investigated in larger longitudinal studies.